2006
DOI: 10.1002/hc.20212
|View full text |Cite
|
Sign up to set email alerts
|

Microwave irradiation assisted facile synthesis of new imidazole, pyrazine, and benzodiazocine derivatives using diaminomaleonitrile

Abstract: Utilizing domestic microwave oven reactions of diaminomaleonitrile with various selected reagents, novel heterocycles such as dicyanopyrazine, 4,5-dicyanoimidazole as well as dicyanobenzodiazocine derivatives were prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Moreover, Alfonsi et al [233] have reported the synthesis of pyrazines derivatives and other series of N-heterocycles 250, 251 by tandem imination/annulation of γ-and δ-ketoalkynes 249. The reaction was achieved by the intramolecular cyclization of 2-acetyl-1-propargylpyrroles in the presence of ammonia Original synthetic heterocycles, such as substituted dicyanopyrazines 247, 248, have been synthesized using a domestic MW oven [232]. The reaction proceeded by a cyclocondensation of diaminomalonitrile with ketones (e.g., acenaphthenequinone, 245) or an ester 246 in the presence of triethylamine in ethanol (Scheme 52), and the expected products were obtained with good to excellent yields.…”
Section: Scheme 48 Mw-assisted Ugi 4-component Reaction Leading To Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Alfonsi et al [233] have reported the synthesis of pyrazines derivatives and other series of N-heterocycles 250, 251 by tandem imination/annulation of γ-and δ-ketoalkynes 249. The reaction was achieved by the intramolecular cyclization of 2-acetyl-1-propargylpyrroles in the presence of ammonia Original synthetic heterocycles, such as substituted dicyanopyrazines 247, 248, have been synthesized using a domestic MW oven [232]. The reaction proceeded by a cyclocondensation of diaminomalonitrile with ketones (e.g., acenaphthenequinone, 245) or an ester 246 in the presence of triethylamine in ethanol (Scheme 52), and the expected products were obtained with good to excellent yields.…”
Section: Scheme 48 Mw-assisted Ugi 4-component Reaction Leading To Pmentioning
confidence: 99%
“…Moreover, they are versatile synthetic intermediates [225], and many functionalized pyrazines possess pharmacological activities, such as antiviral [226,227] (242, 243), ATR kinase inhibitor [228] (244), antitumor [229], vascular endothelial growth factor inhibitory activity [230], or as epithelial sodium channel blockers [231] (Figure 15). Original synthetic heterocycles, such as substituted dicyanopyrazines 247, 248, have been synthesized using a domestic MW oven [232]. The reaction proceeded by a cyclocondensation of diaminomalonitrile with ketones (e.g., acenaphthenequinone, 245) or an ester 246 in the presence of triethylamine in ethanol (Scheme 52), and the expected products were obtained with good to excellent yields.…”
Section: Scheme 48 Mw-assisted Ugi 4-component Reaction Leading To Pmentioning
confidence: 99%
“…Methods of synthesis of imidazoles include a four-component condensation using Wang's resin in refluxing acetic acid; [5] condensation of 1,2-diketones, aldehydes, primary amines, and ammonium acetate in phosphoric acid [6] and in acetic acid; [7] using an organocatalyst in acetic acid, [8] as well as in H 2 SO 4 [9] and dimethyl sulfoxide (DMSO); [10] condensation of benzoin, aldehydes, and ammonium acetate in a variety of catalysts, such as molecular iodine, [11] [Hbim]BF 4 , [12] microwave (MW)/silica gel/NaHSO 4 , [13] MW/AcOH, [14] MW/Et 3 N, [15] and MW/ Al 2 O 3 /NH 4 OAC; [16] and condensation of two different isocyanides in the presence of Cu 2 O. [17] However, many of these procedures suffer from disadvantages, such as harsh reaction conditions, prolonged reaction times, high reaction temperature, and low isolation yields, and the catalysts cannot be recovered and reused in most of the existing methods.…”
Section: Europium Triflate-catalyzed One-pot Synthesis Of 245-trisumentioning
confidence: 99%
“…The synthesized compound was obtained from the reaction of equivalent amounts of 1-methyl-3,5bis[(E)-4-chlorophenylmethylidene]tetrahydro-4(1H)pyridinone with 1 and sarcosine. 11 We have spent a long time on the synthesis of new heterocycles via condensation reactions 1,12 and/or donor-acceptor interaction. [13][14][15][16] Accordingly and in this paper, we have prompted to utilize 1-(dicyanomethylene)acenaphthen-2-one (1) in the synthesis of new heterocyclic compounds which might show prospective biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Condensation of 1 with 5,6-diamino-pyrimidine-2,4diol hemisulphate (11) led to the formation of acenaphtho-[1,2-g]pteridine-9,11-diol (12). Compound 12 exhibited IR absorptions at n = 3512 and 1645 cm -1 which were ascribable to OH and C=N, respectively.…”
Section: Introductionmentioning
confidence: 99%